HUBUNGAN PENGETAHUAN TERHADAP MOTIVASI IBU DALAM PEMBERIAN IMUNISASI DASAR PADA ANAK - Firda " Sari; Ganis " Indriati; Jumaini " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Tuberculosis, diphtheria, pertussis, tetanus, hepatitis and polio are the largest cause of mortality and morbidity in children, so that very important to prevent the occurrence these diseases one of them can be prevented by immunization. This research aims to identify relationship of knowledge with mother’s motivation in giving basic immunization to their children in health care. This research was quantitative by using correlative descriptive method and cross sectional design. This research was conducted in Umban Sari primary health care Pekanbaru by total sample 111 respondents who taken by using cluster sampling technique. The measuring instrument used questionnaire sheet. Analysis used Chi-Square test. The result of Chi-Square showed there was significant relationship between knowledge with mother’s motivation in giving basic immunization to their children (p value 0.000 <α 0.05). The research recommend nurse (or paramedic) health care to increase promoting and monitoring immunization program, increase mother motivation to immunization their children and minimalized factors that could lack motivation. Keywords:Basic immunization, knowledge, motivation